Humor and the critique of knowledge: A pragmatic analysis of Cunk on Life (2024) - Wulan, Retno; Manar, Marsandi; Nugroho, Aji Royan; Pratama, Aryawira (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
Anchored by a theory of nine types of humor systematically proposed by Morrison (2008), this research aimed at analyzing types and functions of humor in a mockumentary series entitled Cunk on Life (2024). This mockumentary depicted humor as not only an entertainment or amusement medium but also social critics to the knowledge, popular culture, and how societies realize the reality. This research employed the qualitative-descriptive approach. The data were obtained through dialogues transcript and context observation of each scene. The findings pointed out that absurd humor, verbal humor, and incongruity humor were dominantly used in Cunk on Life (2024). They all served to highlight ignorance, unawareness, logical contradictions, and the authority of knowledge and the media. In addition, the findings also revealed four main social functions of humor used in this series and elaborated its implication in EFL classroom. This research contributes to the development of pragmatic linguistics and semiotics studies by expanding the application of Morrison's theory to the mockumentary genre, which has rarely been studied academically.